Tourism Development Strategy in Mundeh Kangin Village Sub District Selemadeg Barat, District Tabanan Bali - Sengkey, Fenny; Osin, Rosvita Flaviana (Akademi Komunitas MAPINDO, 2023)
Mundeh Kangin Village has natural resource potential that can be developed into agrotourism. The MundehKangin Village farmer group transformed the village into a durian village. The unique nature and culture attracttourists to visit the village. In improving the quality of tourism, of course there needs to be an effective strategyso that the tourism ecosystem in Mundeh Kangin Village can become a leading tourism destination in TabananRegency, Bali. The focus and aim of this research is to formulate a development strategy for Mundeh KanginVillage. Using the SWOT analysis method (Strength, Weakness, Opportunities, Threats) in analyzing thestrategic environment in the management of Tourism Villages. This research uses a qualitative research typeusing sources from Mundeh Kangin Village, namely the village head (perbekel), the Tourism Awareness Group(POKDARWIS) and farmer groups. Based on the IFE and EFE matrix tables, the total weighted scores are 2.75and 3.12. This shows that agrotourism in Mundeh Kangin Village is relatively strong in overcoming weaknessesand taking advantage of existing opportunities to overcome threats. The internal strategic factor in MundehKangin Village which is the main strength is that it is one of the horticultural commodities which has reachednational and international markets and the garden products in the form of local fruits such as durian, salak,buni, chocolate, coffee, coconut, porang grow abundantly in Mundeh Kangin Village 0.64, while the mainweakness is capital and infrastructure which is still lacking with a total value of 0.33. The external strategicfactor in the development of Mundeh Kangin village which is the main opportunity is the lifestyle of the peoplewho want to return to nature with a value of 0.57, while the main threat faced is the unpredictable climate witha value of 0.30. The research results show that the strategy that can be used by Mundeh Kangin Village is aGeneric expansion strategy. Meanwhile, Strategy variations are, concentric diversification, market penetration,market and product development and backward integration.Keywords: SWOT analysis, development, tourist villages